2015
DOI: 10.1002/chem.201405906
|View full text |Cite
|
Sign up to set email alerts
|

CaO as Drop‐In Colloidal Catalysts for the Synthesis of Higher Polyglycerols

Abstract: Glycerol is an attractive renewable building block for the synthesis of polyglycerols, which find application in the cosmetic and pharmaceutical industries. The selective etherification of glycerol to higher oligomers was studied in the presence of CaO colloids and the data are compared with those obtained from NaOH and CaO. The materials were prepared by dispersing CaO, CaCO3, or Ca(OH)2 onto a carbon nanofiber (CNF) support. Colloidal nanoparticles were subsequently dispensed from the CNF into the reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
(34 reference statements)
1
20
0
Order By: Relevance
“…Purification of the oligoglycerol fractions has been then undertaken. As previously pointed out by B. M. Weckhuysen and co-workers, 12 we observed that at a low conversion the reaction media is nearly colourless but turned to dark brown at a conversion close to 80%. This change of colour was attributed to the formation of side products notably stemming from the dehydration of glycerol and oligoglycerols to readily polymerizable chemicals (exact elucidation of the chemical composition of the black materials was not trivial).…”
supporting
confidence: 86%
“…Purification of the oligoglycerol fractions has been then undertaken. As previously pointed out by B. M. Weckhuysen and co-workers, 12 we observed that at a low conversion the reaction media is nearly colourless but turned to dark brown at a conversion close to 80%. This change of colour was attributed to the formation of side products notably stemming from the dehydration of glycerol and oligoglycerols to readily polymerizable chemicals (exact elucidation of the chemical composition of the black materials was not trivial).…”
supporting
confidence: 86%
“…This could be linked to the fact that the polymerization reaction at higher temperatures released more water, hence promoting the formation of colloidal Ca(OH) 2 according to Equation (1). Further, in the same group, Kirby et al [44] reported that the active phase derived from CaO/CNF catalyst might be the colloidal Ca(OH) 2 particles and Ca 2+ .The amounts of Ca and Mg leaching from dolomite were also determined by ICP-OES during the glycerol polymerization reaction by Barros et al [7]. According to these authors, 49% Ca and 4% Mg leached into the medium at 245 • C after 24 h of reaction.…”
Section: Partial Dissolution Of Heterogeneous Catalystsmentioning
confidence: 98%
“…Several types of catalysts have been reported in the literature to polymerize glycerol to PGs, including strong acids [39][40][41], alkali-modified zeolites [42,43], bulk or supported alkaline oxides [3,5,28,44], alkaline carbonate and hydroxide [21,28,45,46] and impregnated basic mesoporous solids [47]. Among all these catalysts, alkaline homogeneous and heterogeneous catalysts gave better performances than acid catalysts in terms of selectivity to PGs [9,41].…”
Section: Catalytic Systemsmentioning
confidence: 99%
See 2 more Smart Citations